Evaluation and products characterization of mango seed shell and kernel conventional pyrolysis (2020)
With a national production of 361 tons in 2018, mango is a fundamental crop for the development of Colombia, with annual production growth of 20% (Casa Editorial El Tiempo, 2019; MinAgricultura & Agronet, 2019). However, as production increases, so does mango by-products such as seeds. Conventional pyrolysis comes out as a high potential treatment for the conversion of low degradability biomass, such as mango seeds, into added-value products. In this study, the conversion of mango seeds in biochar, bio-oil, and biogas by conventional pyrolysis was evaluated at a wide temperature range (400, 500, 600 and 700?C) and for the different components of the seeds (shell, kernel, and 1:2 mixture). Characterization of biomass (ultimate analysis, FTIR and calorific value) was made. Pyrolytic products were obtained at the optimum temperatures found. Characterization of biochar (ultimate analysis, FTIR and calorific value), bio-oil (GC-MS, FTIR, calorific value and distillation curve) and biogas (composition and calorific value) was also carried out at the optimal temperatures. Biomass fed had a significant effect in production yields, whether temperature had no significant effect over the bio-oil production. At optimum temperatures, bio-oil composition differed between biomasses due to its composition, biogas of kernel pyrolysis had a greater energy value due to the higher temperature set and biochars of the three biomasses fed had similar properties and compositions. High moisture content in bio-oil made it unsuitable for biofuels production unless further treatment is made.